Pyrolysis characteristics and kinetics of palm shell waste mixtures with Mukah Balingian Coal - Amer Nordin Darus, author; Ahmad Hussain, author; Farid Nasir Ani, 1957-, author; International Conference on Energy and Environment (2006 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL